Monumental sounds : art and listening before Dante - Shoaf, Matthew G. (Brill's studies on art, art history, and intellectual history, 2021)
"In Monumental Sounds, Matthew G. Shoaf examines interactions between sight and hearing in spectacular church decoration in Italy between 1260-1320. In this "age of vision," authorities' concerns about whether and how worshipers listened to sacred speech spurred Giotto and other artists to reconfigure sacred stories to activate listening and ultimately bypass phenomenal experience for attitudes of inner receptivity. New naturalistic styles served that work, prompting viewers to give voice to depicted speech and guiding them toward spiritually fruitful auditory discipline. This study reimagines narrative pictures as site-specific extensions of a cultural system that made listening a meaningful practice. Close reading of religious texts, poetry, and art historiography augments Shoaf's novel approach to pictorial naturalism and art's multisensorial dimensions"--